Arterial Blood Gases in Normal Subjects at 2240 Meters Above Sea Level: Impact of Age, Gender, and Body Mass Index - Silvia Cid-Juárez; Norma A. Téllez-Navarrete; Anaid Bautista-Bernal; Pablo León-Gómez; Isabel Salas-Escamilla; Laura Gochicoa-Rangel; Rogelio Pérez-Padilla (Permanyer, 2023)
Background: The values of arterial blood gases (ABG) change with altitude above sea level; empirical verification is essential because ventilatory acclimatization varies with ethnicity and a population's adaptation. Objective: The aim of the study was to describe ABG in a healthy population residing at 2,240 meters above sea level, to identify the mean level of alveolar ventilation (PaCO2), and to know whether a progressive increase in PaCO2 occurs with age and the impact of increasing body mass index (BMI). Methods: We conducted a cross-sectional study in a referral center for respiratory diseases in Mexico City. Associations among variables with correlation coefficient and regression models of PaO2, SaO2, and P(A-a)O2 as dependent variables as a function of age, BMI, minute ventilation, or breathing frequency were explored. Results: Two hundred and seventeen healthy subjects were evaluated with a mean age of 40 ± 15 years, mean of the PaO2 was 71 ± 6 mmHg, SaO2 94% ± 1.6%, PaCO2 30.2 ± 3.4 mmHg, HCO3 20 ± 2 mmol/L, BE-2.9 ± 1.9 mmol/L, and the value of pH was 7.43 ± 0.02. In a linear regression, the main results were PaO2 = 77.5-0.16*age (p < 0.0001) and with aging P(A-a)O2 tended to increase 0.12 mmHg/year. PaCO2 in women increased with age by 0.075 mmHg/year (p = 0.0012, PaCO2 =26.3 + 0.075*age). SaO2 and PaO2 decreased significantly in women with higher BMI 0.14% and 0.52 mmHg per kg/m2, (p = 0.004 and 0.002 respectively). Conclusion: Mean PaCO2 was 30.7 mmHg, implying a mean alveolar ventilation of around 30% above that at sea level.